Experimental Performance Evaluation of an Integrated Solar-Driven Adsorption System in Terms of Thermal Storage and Cooling Capacity - M.T. Nitsas; E.G. Papoutsis; I.P. Koronaki (Energies, 2020)
Heat-driven coolers provide a reliable and environmentally benign alternative to traditional electrically powered chillers. Their main advantage is that they can be driven using low enthalpy heat sources. A solar system is installed at the school of Mechanical Engineering of National Technical University of Athens in order to examine the potential of thermal storage and solar cooling under Athens climatic conditions. The cooling effect is produced using a dual bed, single stage, zeolite/water adsorption chiller with cooling capacity of 10 kW at its nominal conditions of operation. Both vacuum tube collectors and hybrid photovoltaic thermal collectors are installed in order to supply the system with heat. The system is evaluated in terms of solar collectors’ useful energy production, heat stored in the intermediate buffer and cooling system’s performance. It is observed that the cooling system operates satisfactorily under Athens climatic conditions achieving a maximum cooling capacity of 3.7 kW and an average COP around 0.5.